Terang Iman Kristiani dalam Budaya Ti’i Ka, Nagekeo, Flores - Daga, Yohanes (Perspektif, 2021)
In this paper, the author focuses on the theme of the discussion about faith and culture, especially the Ti’i ka culture of the Nagekeo community, Flores. For the author, true faith is a personal human relationship with God in such a way that it brings people into ecclesiastical communion. In this community people unite and gather to live and celebrate faith through common prayers and various rituals involving all members of the Church. The author assumes that all this does not just happen. It all starts with the proclamation of faith. In that proclamation, the cultural factor of the local community becomes important so that the faith can be well accepted by the local community. To explore this theme, the writer uses the method of critical reading and observation. Through this paper the writer wants to convey a message that faith must be entrenched. Faith that has been entrenched will become a unified whole that can create a socio-religious habitus that cannot be separated from the daily life of the local community.